Ungkapan-ungkapan Advertensi Jamu Kuat: Tinjauan Semiotika - Sudin M.Saleh Djumadil; Nirwana Nirwana (Universitas Khairun, 2018)
This research aims to describe and elaborate on the form and meaning of Jamu kuat advertising expressions. The observation method used in this research in order to get the data. The obtaining data are classified and analyzed by using qualitative descriptive analysis method. The results of the research show that there are six jamu kuat advertisements, namely symbol of strength, power, wildness, durable, extra stamina and manliness. All of the symbols being analyzed are based on the linguistic and nonlinguistic sign. Keyword: advertisement, symbol, semiotic